DOP46 Sustainability rate of immunomodulators monotherapy in patients with Crohn's Diseases: A population-based analysis from the epi-IIRN cohort. (27th May 2021) - Atia, O; Friss, C; Mendelovici, A; Shteyer, E; Yogev, D; Ledderman, N; Greenfeld, S; Kariv, R; Loewenberg Weisband, Y; Gabay, H; Nevo, D; Matz, E; et al.
Abstract: Background: Immunomodulators (IMM), including thiopurines and methotrexate (MTX), have been long used to maintain remission in Crohn's disease (CD), both associated with remission, but also with toxicity and therapeutic failure. We aim to compare the sustainability of thiopurines and MTX commenced as monotherapy in patients with CD, and to explore predictors of sustainability. Methods: This study was performed on data from four Health Maintenance Organizations (HMOs), covering 98% of the Israeli population. We included all biologic-naïve CD patients diagnosed after 2005 and treated with IMM monotherapy for at least three months. Sustainability was defined as continues IMM treatment without switching therapy, adding biologics or requiring surgery. In addition, at most one short steroid course was allowed. Cox regression model was used to explore estimated predictors to sustainability. To compare sustainability rate between thiopurines and MTX we used propensity score (PS) matching, and thereafter Cox regression model. Results: A total of 4, 891 (1, 551 [32%] pediatric-onset and 3, 340 [68%] adults) IMM-treated patients were included with 37, 825 person-years of follow up, of whom 4, 339 (89%) were treated with thiopurines and 552 (11%) with MTX. The median time from CD diagnosis to initiation of IMM was 6.1 months (IQR 1.7–19.7), and the median course duration was 11.9 months (6.1–25.3). Sustainability rate was recorded in 92% of patients after 6 months from initiation of IMM and 81%, 69% and 65% at one, three and five years, thereafter. The most common type of failure was escalation to biologics (67%), while 17% required repeated steroid courses and 15% underwent surgery. Sustainability was associated with earlier initiation of IMM during the disease course (HR 0.98 [95%CI 0.97–0.985]) and lack of steroids at initiation of IMM (HR 0.7 [95%CI 0.6–0.8]). A PS adjusted analysis that included 337 thiopurnes-treated patients individually matched with 337 MTX-treated patients, showed sustainability was significantly better with thiopurines (HR 0.7 [95%CI 0.5–0.8]). Conclusion: Two thirds of biologic-naïve CD patients treated with IMM monotherapy sustain this treatment after five years, especially when initiated early during the disease course. Sustainability was more likely in those treated with thiopurines compared with MTX.